9 novembre : journée internationale de solidarité avec le peuple et les étudiants du Cambodge
'Cambodge' written in round typeface; letter 'b' extended so it resembles a stem, with flower at the end. Map of Cambodia at the centre of the flower Poster advertising the day of solidarity with Cambodia, 9 November PO-1383